2021
DOI: 10.1002/elsa.202100130
|View full text |Cite
|
Sign up to set email alerts
|

Formic acid reduction and CO2 activation at Mo2C: The important role of surface oxide

Abstract: Small organic acids, such as formic or acetic acid, which are well‐known products of the electrochemical CO2 reduction reaction, are often not further reduceable to their respective alcohols. Alcohols are well‐desired chemicals and useful as fuels, since they can be easily purified and provide a high energy density. Here, we present a combined electrochemical, differential electrochemical mass spectrometry (DEMS), and nuclear magnetic resonance spectroscopy (NMR) study, providing insight in the electro‐reducti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 35 publications
0
10
0
Order By: Relevance
“…For all experiments, a PEEK flow cell (Hiden Analytical, U.K.) with a constant electrolyte flow rate of 50 μL min –1 was used. Further information on the setup and the delay time can be found elsewhere. A Metrohm Autolab (PGSTAT 302N) was used as potentiostat. The scan rate was 2 mV s –1 , and the m / z signals of 2 (hydrogen, H 2 + ), 15 (methane, CH 3 + ) and 26 (ethylene, C 2 H 2 + ) were simultaneously recorded.…”
Section: Methodsmentioning
confidence: 99%
“…For all experiments, a PEEK flow cell (Hiden Analytical, U.K.) with a constant electrolyte flow rate of 50 μL min –1 was used. Further information on the setup and the delay time can be found elsewhere. A Metrohm Autolab (PGSTAT 302N) was used as potentiostat. The scan rate was 2 mV s –1 , and the m / z signals of 2 (hydrogen, H 2 + ), 15 (methane, CH 3 + ) and 26 (ethylene, C 2 H 2 + ) were simultaneously recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The polycrystalline electrocatalyst was synthesized according to previous publications. , Here, Mo (99.95%, Advent Ltd.) carburization was performed in a home-built, vacuum-assisted quartz furnace, which allows the transfer of electrodes into the glovebox under a H 2 atmosphere after the synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…40 It has, however, been reported that on select catalysts, formic acid can be reduced to methanol, albeit with low current density and poor selectivity. [41][42][43] The primary difficulty with formate/formic acid as a product is the need for intricate separation procedures, which is further complicated in the decoupled system by the redox meditator. It is desirable for the mediator to be indefinitely reusable in a semi-closed system where only CO 2 and water are added and products are collected.…”
Section: Mechanistic Insightsmentioning
confidence: 99%